Corporate Secrets and the Ambiguity of Article 23: A Critical Analysis of KPPU’s Interpretation - Anna Maria Tri Anggraini; Ahmad Sabirin; Verandha Mayva; Jimi Rambo R. Arranchado (Universitas Negeri Semarang, 2026)
This paper examines the application of the company secret concepts in KPPU decisions number 19/KPPU-L/2007, number 35/KPPU-I/2010, and Number 8/KPPU-L/2024, and how KPPU determines the corporate secrets. This paper employs a normative approach utilising secondary data supported by primary data from interviews with KPPU. The interesting findings indicate that the guidelines of Article 23 of Law Number 5 of 1999 remain unratified in regulations, often leading to company secrets and their criteria being equated with trade secrets as regulated in Law Number 30 of 2000 on Trade Secrets. Then, the objects of corporate secrets differ in the three decisions; the three discuss corporate secrets that must be kept confidential due to their economic value, potentially causing company losses if made public. The paper recommended that the amendments to Law No. 5 of 1999 should include a distinct definition of “company secrets” aligned with global business developments and international best practices. Furthermore, KPPU should adopt a structured rule-of-reason analysis in assessing Article 23 violations by considering the economic impact of information leakage, the perpetrator’s intent, and proportionality to competitive harm to ensure predictability and prevent abuse of authority.